Identifikasi Wilayah Unggulan Lumbung Pangan Komoditas Padi Provinsi Sumatera Selatan (LQ dan Shift-Share Analysis 2020-2024) - Inaya Marsha Mudhiah; Hanifah Marsha Mudita (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Population growth and land-use conversion continue to pressure rice production in Indonesia, increasing the need to identify priority regions for Kawasan Sentra Produksi Pangan (KSPP), Indonesia’s Food Production Center Zones under the 2025–2029 National Medium-Term Development Plan. This study aims to identify priority areas for rice-based food production in South Sumatra Province using a descriptive-quantitative approach. The analysis applies Location Quotient (LQ) and Shift-Share Analysis (SSA) to assess specialization, competitive performance, and structural growth of rice production across districts and cities from 2020 to 2024. The results indicate that South Sumatra records an average rice LQ of 0.92 relative to the national level, showing that rice has not yet become a national-scale base commodity despite notable spatial disparities. SSA results reveal strong regional contrasts. East OKU District records the highest Competitive Effect at 59,533 tons, while Banyuasin District records the highest Industrial Mix Effect at 37,545 tons, indicating rapid growth aligned with the provincial food-crop structure. The integration of LQ and SSA identifies six priority areas: Ogan Ilir, Ogan Komering Ilir, Pagar Alam, Muara Enim, Penukal Abab Lematang Ilir, and East OKU District. The novelty of this study lies in producing a province-wide priority mapping based on a single strategic commodity. The analysis is limited by its focus on three food crops and by the exclusion of biophysical factors. Despite these limitations, the findings provide an empirical basis for determining KSPP priority zones and guiding rice-based regional development planning.